Comparision between HbA1c and Fasting Blood Sugar as diagnostic marker in prediabetes - Naik, Srinivas; K, Kamble T.; kumar, Sunil; Acharya, Sourya (International Journal of Psychosocial Rehabilitation, 2020)
We are going to compare the HbA1 c and Fasting Blood Sugar in diagnosis of prediabetes and conclude that which test is better in early diagnosis of prediabetes.Correlate HbA1c and Fasting blood sugar with cardiovascular risk factor in prediabetes it is a cross sectional study done in an institutional setup, we use FBS,HbA1c,FLP and other anthropometric values, like waist circumference, hip circumference and waist and hip ratio. we are making an attempt to prove HbA1c is better diagnostic test compare to FBS in early diagnosis of prediabetes and preventing progression to diabetes.conclusion not yet arrived, still the study is in process